BaeR participates in cephalosporins susceptibility by regulating the expression level of outer membrane proteins in Escherichia coli. (3rd September 2020) - Wang, Shuaiyang; You, Chunbo; Memon, Fareed Qumar; Zhang, Geyin; Sun, Yawei; Si, Hongbin
Abstract: The two-component system BaeSR participates in antibiotics resistance of Escherichia coli . To know whether the outer membrane proteins involve in the antibiotics resistance mediated by BaeSR, deletion of acrB was constructed and the recombined plasmid p- baeR was introduced into E. coli K12 and K12△ acrB . Minimum inhibitory concentrations (MICs) of antibacterial agents were determined by 2-fold broth micro-dilution method. Gene expressions related with major outer membrane proteins and multidrug efflux pump-related genes were determined by real-time quantitative reverse transcription polymerase chain reaction. The results revealed that the MICs of K12Δ acrB to the tested drugs except for gentamycin and amikacin decreased 2- to 16.75-folds compared with those of K12. When BaeR was overexpressed, the MICs of K12Δ acrB /p- baeR to ceftiofur and cefotaxime increased 2.5- and 2-fold, respectively, compared with their corresponding that of K12△ acrB . At the same time, the expression levels of ompC, ompF, ompW, ompA and ompX showed significant reduction in K12Δ acrB /p- baeR as compared with K12△ acrB. Moreover, the expression levels of ompR, marA, rob and tolC also significantly 'decreased' in K12Δ acrB /p- baeR . These findings indicated that BaeR overproduction can decrease cephalosporins susceptibility in acrB -free E. coli by decreasing the expression level of outer membrane proteins. Graphical Abstract: